Divisive yet also invisible? The Franco-Spanish border of the Basque-speaking area through the prism of nuptial mobility (1780-1920) - Duinat, Benjamin (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
Through the systematic study of the frequency of cross-border marriages, between 1780 and 1920 in the valley of Xareta straddling the Franco-Spanish border, we aim to revise the dominant interpretation according to which the frontier population of the Basque country turned their back on their neighbours during the 19th century. The permanence and regularity of cross-border nuptial unions show that remarks about the establishment of a permanent territorial divide between Basques in France and Spain do not relate to a real fact and are thus erroneous impressions that have been repeated uncritically. Ultimately, the border is polysemic, as the range of actors and groups apprehended and appropriated it very differently. When analysing the spatial dynamics linked to nuptial mobility, the dividing line of the State is almost invisible.
Keywords: Boundary; Nuptial Mobility; Basque-speaking área; 18th-20th centuries